Trade Union Advisory Medical Officers - Morgan, H. B. (Hyacinth Bernard Wenceslaus Morgan), 1885-1956
1920 1920 1920s 9 pages (4) Place and function of Charity (5) General Medical treatment of general population. (6) Labour colleges (lectures on Public Health from the Labour point of view). 3. It is difficult in dealing with the relationship between Labour and Medicine in its protean aspects to avoid a general dissertation on the whole aspect of the Medical profession to the community, but it is hoped in this memorandum to confine the issue to the specific aspects bearing on ths scheme now being submitted. 4. It may be permitted, however, to remark that the medical treatment even under present conditions of a large section of the community, including the workers, is not regarded as satisfactory. And the perusal of Sir George Newman's memorandum on Medical Education will demonstrate from the mouth of one of the sympathisers of the present system that in the bourgeois system there are grave defects in the system of education and training of the medical profession and in the treatment especially of environmental disease. The individual general medical practitioner, and frequently indeed the medical profession as a whole, is often regarded with disapproval by a certain section of the public. The blame should rather be attached to the system which produces the type of general practitioner disapproved of. The same system which is responsible for the economic exploitation of the worker is responsible for the faulty method of medical education and the results arising therefrom. INTERNATIONAL MEDICINE. It is important that the Labour Movement should in its encouragement of the ideal of international brotherhood have some interest in international medicine, or in the way by which disease from one set of workers in one country may be conveyed either by direct contact or by handling of commodities to the workers of another. Some Trade Unions, like the Seamen's and Firemen's Union, the Dockers' Union, the Transport Workers, etc. ought to be specially interested in that part of the subject. It is important that Labour should have someone on its General Staff specially interested and whose work is specially devoted to considerations favourable to or antagonistic to the workers arising out of questions of International Health. The ideal to aim at is to effect some sort of liaison with the Medical Section of the International Labour Bureau of the League of Nations, the International Red Cross Movement, and with the Society of the Medical Officers of Health (through the Port Sanitary Medcial [Medical] Officers of Health and other M.O.Hs.) One special subject may be mentioned. Clinics for the treatment of Venereal Diseases are being set up in various districts. It is said that workers on board ship, owing to the temptations of their vocation are especially liable to be numbered among the victims of this disease. Every facility should be afforded for the treatment of these venereal diseases free among workers in ship and dockyard - and that the Labour Movement should prove its interest in these devastating diseases with their number of innocent victims, by suggesting or advising as to the sites of these centres, the development of propaganda to the workers concerned and in other ways. One function of an Advisory Medical Staff would be to keep an eye on such a development. 36/H24/11